IMPACT OF HIV/AIDS ON ECONOMIC GROWTH IN RWANDA - KABALISA, Michel (My University, 2011)
Impact assessment is widely used in the field of socio-economic development. Socioeconomic impact of HIV/AIDS has taken on similar cross-cutting studies mostly in poverty, gender and environment disciplines by applying various quantitative techniques tools including econometric modelling. An extensive literature review was carried out and reveals, in many cases, a strong socioeconomic impact of HIV/AIDS on the economic output in the long run. Drawing on existing methodologies, two models are developed: Spectrum Policy modeler has been applied to determine the HIV/AIDS epidemiologic impact. An econometric model that integrates the determinants variables of the HIV/AIDS Epidemiology and the Gross Domestic Product (GDP) and simulates different scenarios which represent a variety of HIV/AIDS levels corresponding to hypothesised behaviours. This econometric model demonstrates a limited impact of HIV/AIDS on GDP in the context of extended use of antiretroviral therapy combined with a strong preventive policy which would likely curb the HIV in short term to mid-term. It also highlights the impact of other essential determinant factors on GDP, which are included in the model that decision-makers should act upon in order to stimulate the economic growth
MM - P&DM
Keywords: HIV/AIDS in Rwanda; Economic growth, Rwanda